Răspuns :
10 110
p1=p + ------ * p => p1= -------- * p
100 100
10 110*p 10*(110p/100) 99p
p2= p1 - ------ * p1 = ---------- - ---------------------- = --------- = 1980
100 100 100 100
99p
------- = 1980 => 99p=198000 => p = 2000
100
p1=p + ------ * p => p1= -------- * p
100 100
10 110*p 10*(110p/100) 99p
p2= p1 - ------ * p1 = ---------- - ---------------------- = --------- = 1980
100 100 100 100
99p
------- = 1980 => 99p=198000 => p = 2000
100
10 110
p1=p + ------ * p => p1= -------- * p
100 100
10 110*p 10*(110p/100) 99p
p2= p1 - ------ * p1 = ---------- - ---------------------- = --------- = 1980
100 100 100 100
99p
------- = 1980 => 99p=198000 => p = 2000
100
p1=p + ------ * p => p1= -------- * p
100 100
10 110*p 10*(110p/100) 99p
p2= p1 - ------ * p1 = ---------- - ---------------------- = --------- = 1980
100 100 100 100
99p
------- = 1980 => 99p=198000 => p = 2000
100